The Influence Of Utilization Of Information Communication Technology (ICT) Towards Work-Life Balance Satisfaction - Nur Ismaniza Akma, Salam (Universiti Malaysia Sarawak (UNIMAS), 2020)
Technology has become an important part of people's lives. It allows everyone to share information or to access new information. Everyone uses technology on a daily basis for education, communication, job, or business. With the invention of mobile phones and the internet, everyone can use technology to communicate with their family and friends. Technology has changed the way of communication. The aim of this study is to study the influence of utilization of Information Communication Technology (ICT) towards work-life Balance satisfaction. This study was conducted in a public school which involves 108 respondents. The statistical analysis which is Pearson Correlation used to test the hypotheses. Statistical Package for Social Sciences (SPSS) version 26 is used for analyzing the data. The findings show that accessibility to work and maintaining personal relationships does have a significant relationship with respondent’s work-life balance satisfaction. The implication of this study is that bring insight to the employers and employees on how technology can influence work-life balance satisfaction and how to ensure work-life balance is not affected by technology.